Evaluation of the Antioxidant Activity of a Leaf Extract of Cranberry (Vaccinium macrocarpon) - Kushwaha, Kundan Kumar; Saini, Rita; Patil, Shivanand M. (Journal for Research in Applied Sciences and Biotechnology, 2024)
Introduction: Cranberry (Vaccinium Macrocarpon) is one of the extremely accessible conventionally used herbal plants with various biological activities. However, actions of Cranberry on antioxidant properties and chemically investigated for its phytoconstituents in the current studied. Therefore, the scope of the current exploration is to screen the antioxidant effects of leaf extracts. Materials and Methods: The antioxidant activity (in vitro) was assessed with UV Spectroscopic. Hydrogen peroxide (free radical) scavenging methods were employed to check the in vitro antioxidant property. Result: Plant methanol, Ether and Distilled water extract had a substantial impact on the hydrogen peroxide radical activity of scavenging and less effects than the standard radical activity and the bioactive compound like flavanoids, tannins and glycosides were shown to be positive. Conclusion: These findings suggested that the plant leaves are comprised of significant antioxidant properties. It could be a promising source for the existence of antioxidant properties and other therapeutic agents.